Effects of Demo Kit on Remediating Senior School Students’ Misconceptions in Mitosis and Meiosis in Ilorin, Nigeria - Luwoye, Akindeyi; Bello, Ganiyu; Adeoye, Gabriel Ademakinwa (Journal of Learning for Development, 2021)
This study investigated the effects of demo kit on remediating misconceptions held by senior school students’ in mitosis and meiosis. The quasi-experimental design of the pre-test, post-test, non-equivalent control group was adopted for the study. Multistage sampling technique was used to select 60 male and female biology students from two senior secondary schools in Ilorin metropolis. The instruments used for data collection was Mitosis and Meiosis Achievement Test (MMAT). Frequencies and chi-square were used to answer the research questions and test the null hypothesis respectively. The findings revealed that biology students’ held misconceptions on mitosis and meiosis before and after instructions. However, there was a significant difference in the number of misconceptions held by students taught using demo kit and those taught with the conventional method. It was recommended that biology teachers adopt the use of the demo kit for remediating students pre- and post-instructional misconceptions on mitosis and meiosis.